Big news: Climate change and the business cycle - Alexander M. Dietrich; Gernot J. Müller; Raphael Schoenle (University of Tübingen, Faculty of Economics and Social Sciences, 2023)
News drive expectations about the economy's future fundamentals. Climate change is big news: it will impact the economy profoundly but the effect will take some time to materialize in full. Climate-change expectations thus offer a unique opportunity to study the impact of news on the business cycle. We measure these expectations in a representative survey of US consumers. Respondents expect not much of an impact on GDP growth, but perceive a high probability of costly, rare disasters-suggesting they are salient of climate change. Furthermore, expectations vary systematically with socioeconomic characteristics, media consumption, various information treatments and over time. We calibrate a New Keynesian model with rare disasters to key results of the survey and find that shifts in climate change expectations operate like demand shocks and cause sizeable business cycle fluctuations.
urn:nbn:de:bsz:21-dspace-1386521
Keywords: E43; E52; E58; 330; Climate change; Disasters; Expectations; Survey; Monetary policy; Business Cycle; Natural rate of interest